Maltodextrin-based carbohydrate oral rinsing and exercise performance: systematic review and meta-analysis - Hartley, C.; Carr, A.; Bowe, S. J.; Bredie, W. L. P.; Keast, R. S. J. (Sports Medicine, 2022)
Background: Carbohydrates are an important fuel for optimal exercise performance during moderate- and high-intensity exercise; however, carbohydrate ingestion during high-intensity exercise may cause gastrointestinal upset. A carbohydrate oral rinse is an alternative method to improve exercise performance in moderate- to high-intensity exercise with a duration of 30-75 min. This is the first systematic review and meta-analysis to comprehensively examine the isolated effect of maltodextrin-based rinsing on exercise performance. Objective: The objective of this review was to establish the effect of a maltodextrin-based carbohydrate oral rinse on exercise performance across various modes of exercise. Furthermore, a secondary objective was to determine the effects of moderators [(1) participant characteristics; (2) oral rinse protocols; (3) exercise protocol (i.e. cycling, running etc.) and (4) fasting] on exercise performance while using a maltodextrin-based, carbohydrate oral rinse. Methods: Five databases (MEDLINE, PsycINFO, Embase, SPORTDiscus and Global Health) were systematically searched for articles up to March 2021 and screened using Covidence (a systematic review management tool). A random effects robust meta-analysis and subgroup analyses were performed using Stata Statistical Software: Release 16. Results: Thirty-five articles met the inclusion criteria and were included in the systematic review; 34 of these articles were included in the meta-analysis. When using a conventional meta-analytic approach, overall, a carbohydrate oral rinse improved exercise performance in comparison with a placebo (SMD = 0.15, 95% CI 0.04, 0.27; p = 0.01). Furthermore, when implementing an adjusted, conservative, random effects meta-regression model using robust variance estimation, overall, compared with placebo, a carbohydrate oral rinse demonstrated evidence of improving exercise performance with a small effect size (SMD = 0.17, 95% CI - 0.01, 0.34; p = 0.051). Conclusion: This systematic review and meta-analysis demonstrates that a maltodextrin-based carbohydrate oral rinse can improve exercise performance. When comparing the two meta-analytic approaches, although non-significant, the more robust, adjusted, random effects meta-regression model demonstrated some evidence of a maltodextrin-based carbohydrate oral rinse improving exercise performance overall.